Water Futures: Contention in the Construction of Productive Infrastructure in the Peruvian Highlands - Rasmussen, Mattias Borg (Anthropologica, 2017)
This article explores the potential construction of a water reservoir in Peru’s Cordillera Blanca. Proposed by a peasant group, it would have served important productive purposes but have its intake within the perimeter of a national park. Thus, different notions about water and landscape emerge in the encounters between place-based practices and state-sponsored conservation efforts. Empirically tracing the efforts to construct the reservoir, the analytical focus of the article is on how different ways of knowing water within a particular landscape conjure and collide in the process. It is argued that the movement of water extends itself beyond the physical properties of the reservoir and irrigation channels as these are produced in encounters between different notions of the role of water in the landscape.